2017
DOI: 10.4103/jcrt.jcrt_423_17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous hydrogen sulfide on the proliferation and invasion of human Bladder cancer cells

Abstract: Exogenous H2S may promote cell proliferation and invasion by upregulating the expression level of MMP2 and MMP9 in human bladder cancer EJ cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 0 publications
0
19
0
1
Order By: Relevance
“…However, in contrast, and despite the anticancer efficacy in various types of cancer cells (e.g., gastric carcinoma, renal tumor), other studies have shown that H 2 S may induce tumor cell proliferation, and migration, as well as angiogenesis, via inhibiting apoptosis (122124). Jia et al observed hepatoma cell suppression when CBS/H 2 S pathway was inhibited (125).…”
Section: Biological Properties Of Hydrogen Sulfidementioning
confidence: 96%
“…However, in contrast, and despite the anticancer efficacy in various types of cancer cells (e.g., gastric carcinoma, renal tumor), other studies have shown that H 2 S may induce tumor cell proliferation, and migration, as well as angiogenesis, via inhibiting apoptosis (122124). Jia et al observed hepatoma cell suppression when CBS/H 2 S pathway was inhibited (125).…”
Section: Biological Properties Of Hydrogen Sulfidementioning
confidence: 96%
“…Besides, treatment of thyroid cancer cells with 25-50 µM NaHS effectively enhances migration and invasion by activating PI3K/AKT/mTOR and MAPK pathways [127]. The H2S donor-mediated cell migration has also been confirmed by elevated levels of MMP-2 and -9 protein levels in bladder cancer and esophageal carcinoma following administration of NaHS [18,175,188]. The cell migration-induced activation of AKT pathways have also been reported in multiple myeloma cells following the administration of NaHS [174].…”
Section: H 2 S Donor Enhances Cell Migration and Invasionmentioning
confidence: 99%
“…Exogenous H 2 S also significantly increased cell proliferation and invasion, and MMP-2 and MMP-9 protein expression in the EJ human bladder cancer cell line. These events were increased with higher exogenous H 2 S dosages, suggesting that H 2 S increases the proliferative, invasive, and metastatic capacities of UBC [ 62 ].…”
Section: H 2 S and Cancermentioning
confidence: 99%